Daily meaningfulness among patients with opioid use disorder: Examining the role of social experiences during residential treatment and links with post-treatment relapse. (August 2021) - Knapp, Kyler S.; Brick, Timothy R.; Bunce, Scott C.; Deneke, Erin; Cleveland, H. Harrington
Highlights: Nearly half of end-of-day meaningfulness variability was within-person. End-of-day meaningfulness was higher on days with more positive social experiences. Patients who relapsed had greater meaningfulness reactivity to negative experiences. Individual differences in negative meaningfulness reactivity may indicate risk. Strategies to de-couple negative social experiences and meaningfulness are needed. Abstract: Background: A sense of meaningfulness is an important initial indicator of the successful treatment of addiction, and supports the larger recovery process. Most studies address meaningfulness as a static trait, and do not assess the extent to which meaningfulness might vary within an individual, or how it may vary in response to daily life events such as social experiences. Methods: Ecological momentary assessment (EMA) was used to: 1) examine the amount of within-person variability in meaningfulness among patients in residential treatment for prescription opioid use disorder; 2) determine whether that variability was related to positive or negative social experiences on a daily basis; and 3) assess whether those day-to-day relationships were related to relapse at four months post-treatment. Participants ( N  = 73, 77% male, M age  = 30.10, Range  = 19–61) completed smartphone-based assessments four times per day for 12 days. Associations among social experiences, meaningfulness, and relapse were examined using multilevel modeling. Results: Between-person variability accounted for 52% (95% CI = 0.35, 0.67) of variance in end-of-day meaningfulness. End-of-day meaningfulness was higher on days when participants reported more positive social experiences (β = 1.17, SE  = 0.33, p  < .05, ΔR 2  = 0.041). On average, participants who relapsed within four months post-residential treatment exhibited greater within-day reactivity to negative social experiences (β = −1.89, SE  = 0.88, p  < .05, ΔR 2  = 0.024) during treatment than participants who remained abstinent. Conclusion: Individual differences in maintaining meaningfulness day by day when faced with negative social experiences may contribute to the risk of relapse in the early months following residential treatment.